2018
DOI: 10.1155/2018/2752945
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanical Properties after FS-LASIK with Residual Bed Thickness Less Than 50% of the Original Corneal Thickness

Abstract: Background. The changes in corneal biomechanical properties after LASIK remain an unknown but important topic for surgical design and prognostic evaluation. This study aims to observe the postoperative corneal biomechanical properties one month after LASIK with amount of corneal cutting (ACC) greater than 50% of the central corneal thickness (CCT). Methods. FS-LASIK was performed in 10 left rabbit eyes with ACC being 60% (L60) and 65% (L65) of the CCT, while the right eyes (R) were the control. After 4 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…8, rabbit corneal elastic modulus ranged from 0.16 to 0.60 MPa when IOP increased from 7 to 35 mmHg. Corneal elastic moduli were usually obtained from corneal uniaxial tensile test or corneal inflation tests, and the range of normal rabbit corneal elastic modulus ranged from 0.1 to 0.36 MPa in different studies [7, 24, 3235]. Corneal elastic modulus extracted from this study has the same magnitude with the results reported by the literature.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…8, rabbit corneal elastic modulus ranged from 0.16 to 0.60 MPa when IOP increased from 7 to 35 mmHg. Corneal elastic moduli were usually obtained from corneal uniaxial tensile test or corneal inflation tests, and the range of normal rabbit corneal elastic modulus ranged from 0.1 to 0.36 MPa in different studies [7, 24, 3235]. Corneal elastic modulus extracted from this study has the same magnitude with the results reported by the literature.…”
Section: Discussionsupporting
confidence: 76%
“…Corneal biomechanical properties play an important role in maintaining the normal shape and function of cornea. Besides, the occurrence and development of ocular diseases such as keratoconus, myopia and pseudoexfoliation syndrome, the design and prognosis of corneal surgeries such as corneal transplantations, corneal refractive surgery and corneal collagen crosslinking surgery are also correlated to corneal biomechanics [17]. Therefore, more and more ophthalmologists and researchers expect to obtain human corneal biomechanics though simple clinical measurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the higher the corrected diopter is, the larger the amount of corneal cutting need to take, and the thinner the residual bed thickness of cornea is left. And relatively, the greater the amount of corneal cutting is, the more significant the changes of corneal biomechanical properties will be [2,24] . In addition, previous studies [25,26] have proved IOP measurements were not only associated with CCT, but also affected by corneal mechanical properties.…”
Section: Discussionmentioning
confidence: 99%